Comparison of continuous interscalene block and subacromial infusion of local anesthetic for postoperative analgesia after open shoulder surgery. (23rd January 2017) - Baskan, Semih; Cankaya, Deniz; Unal, Hidayet; Yoldas, Burak; Taspinar, Vildan; Deveci, Alper; Tabak, Yalcin; Baydar, Mustafa
Purpose: This study compared the efficacy of continuous interscalene block (CISB) and subacromial infusion of local anesthetic (CSIA) for postoperative analgesia after open shoulder surgery. Methods: This randomized, prospective, double-blinded, single-center study included 40 adult patients undergoing open shoulder surgery. All patients received a standardized general anesthetic. The patients were separated into group CISB and group CSIA. A loading dose of 40 mL 0.25% bupivacaine was administered and patient-controlled analgesia was applied by catheter with 0.1% bupivacaine 5 mL/h throughout 24 h basal infusion, 2 mL bolus dose, and 20 min knocked time in both groups postoperatively. Visual analog scale (VAS) scores, additional analgesia need, local anesthetic consumption, complications, and side effects were recorded during the first 24 h postoperatively. The range of motion (ROM) score was recorded preoperatively and in the first and third weeks postoperatively. Results: A statistically significant difference was determined between the groups in respect of consumption of local anesthetic, VAS scores, additional analgesia consumption, complications, and side effects, with lower values recorded in the CISB group. There were no significant differences in ROM scoring in the preoperative and postoperative third week between the two groups but there were significant differences in ROM scoring in the postoperative first week, with higher ROM scoring values in the group CISB patients. Conclusion: The results of this study have shown that continuous interscalene infusion of bupivacaine is an effective and safe method of postoperative analgesia after open shoulder surgery.